Perbedaan Kecerdasan Interpersonal antara Siswa Anggota Ambalan dan Bukan Siswa Anggota Ambalan - Intan Dwi Retri Darmawiyanti; Nuraini Nuraini (Ideas Publishing, 2023)
One of the activities that can train students interpersonal intelligence is scouting extracurricular activities. This study aims to compare differences in interpersonal intelligence between students who are members of the troop and those who are not. The research methodology uses a comparative quantitative approach, namely testing data using a questionnaire and comparative analysis of interpersonal conflict scores from the two groups of students. The results showed that there were significant differences in interpersonal intelligence between students who were members of the ambulance and who were not members of the ambulance. Troop members gradually emphasize the importance of interpersonal skills such as effective communication, teamwork, and good relationships with others.